Correlative Analysis of Atherogenic Dyslipidemia among the Patients with Non Alcoholic Fatty Liver Disease Visiting Tertiary Care Center - Risal, Prabodh; Pandey, Medha; Shrestha, Suraj Makaju; Adhikari, Akash; Manandhar, Saroj; Karki, Subindra; Bhatt, Rajendra Dev (Birat Journal of Health Sciences, 2020)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is one of the most prominent causes of chronic liver disease. It is known that dyslipidemia in NAFLD patients may have more severe atherogenic potential with high triglyceride and low density lipoprotein (LDL) as well as less high density lipoprotein (HDL) level. Objective: To determine the atherogenic dyslipidemia and associated factors among patients with NAFLD, Visiting Tertiary Care Center Methodology: Prospective cross-sectional study was conducted at Dhulikhel Hospital-Kathmandu University Hospital (DH-KUH) from January, 2016 to December, 2016. All the patients (n= 973) diagnosed to have fatty liver during this study period were initially enrolled in this study. Patients were further asked to fill up the questioner. Out of total 973 cases, 169 patients were identified as NAFLD. Fasting blood sample and anthropometric measurements (BMI, WHR) were taken. After adjusting exclusion criteria, refusal to participate and dropout from the study, 101 patients and 92 apparently healthy age sex matched control group was selected for the study. Blood sugar level and lipid profile were analyzed to assess the risk of athrogenicity among the NAFLD. Result: High total cholesterol was found in 64.4 %, High LDL was found in 20.8 %, Low HDL is present in 72.2% and high triglyceride is present in 65.8 % patients with NAFLD. Non-HDL cholesterol was significantly higher in NAFLD compared to control group (116.75 ± 34.38 vs. 137.63 ± 39.76, p=0.00). Similarly, calculated cardiac risk ratio (TC/HDL) was significant higher (4.15 ± 1.18 vs. 5.25 ± 1.78, p=0.00) whereas atherogenic index of plasma (AIP) was higher (0.30 ± 0.13 vs. 0.33 ± 0.19, p=0.37). Conclusion: NAFLD is significantly associated with atherogenic dyslipidemia. Calculated cardiac risk and AIP is higher in patients with NAFLD. Therefore it may be helpful to assess dyslipidemia among the patients with NAFLD to prevent cardiovascular events.